PERAN PEMIMPIN DINAS TENAGA KERJA DALAM MENGATASI PEMUTUSAN HUBUNGAN KERJA (PHK) AKIBAT PANDEMI DI KOTA PEKANBARU - Hadinta Walram; Khairul Amri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Termination of Employment Relations is the termination of employment relations due to a certain matter which results in the end of the rights and obligations between the worker or laborer and the entrepreneur. As for the purpose of writing this thesis, namely: to find out the roles and obstacles of the leadership of the Manpower Office in overcoming Termination of Employment (PHK) Due to the Pandemic in Pekanbaru City. This research is a qualitative research. This research was conducted at the Pekanbaru City Manpower Office. The techniques used to collect data in this study are (1) Interview, (2) and Observation. The conclusion of this study shows that the role of the Manpower Office in overcoming Termination of Employment (PHK) Due to the Pandemic in Pekanbaru City is measured using interpersonal roles, roles related to information, and the role of decision makers, has not gone well, namely there is still a lack of decision making Disnaker in dealing with Termination of Employment (PHK) Due to the Pandemic. Keywords: Role, Employment Service, Layoffs, Pandemic